Development of HOTS- and TPACK-Based Learning Devices for Teaching Parabola: A 4-D Model Approach - Pamungkas, Sugeng Adi; Panggabean, Ellis Mardiana; Irvan, Irvan (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2024)
This research aims to develop HOTS- and TPACK-based learning devices for parabola material and to evaluate their validity, effectiveness, and student responses. Using a development research design, the study adopted the Thiagarajan 4-D model, which includes the stages of define, design, develop, and disseminate. The products developed consisted of a lesson plan (RPP), student worksheets (LKPD), and a HOTS-based assessment instrument. Validation by experts indicated that the learning devices met the criteria for validity, with average scores of 4.34 for the lesson plan, 4.24 for the student worksheet, and 4.17 for the HOTS assessment. The effectiveness of the learning devices was examined through two implementation trials with Grade XI students at SMK YPT Pangkalan Brandan. Results showed that 90.4% of students achieved mastery in Trial II, with learning objectives met for each item (84.76% and 84.29%). Student responses were highly positive, reaching 94%, and the learning time did not exceed the school’s standard duration. Improvement in HOTS abilities was also evident, increasing from 52.4% mastery in Trial I to 90.4% in Trial II. Overall, the findings demonstrate that the developed HOTS- and TPACK-based learning devices are valid, effective, and well-received by students. These learning tools can be used to enhance mathematical reasoning, problem-solving skills, and higher-order thinking in parabola instruction.